Practical training report land and survey Kota Samarahan / Teodora Chela Tiyus - Tiyus, Teodora Chela (University Technology MARA Sarawak, 2014)
Land and Survey is the department or organization that deals with the matter of land in Sarawak. With twelve branches all over Sarawak, Land and Survey become the important part of the government since it playing important roles in implementing the land code in Sarawak. There are various sections under the Land and Survey. It includes the registry section, land 1 section, land 2 section, administration section, evaluation section, planning section, fl' section, public relation section, survey section and enforcement section.